Peran Kepala Sekolah dalam Pemberdayaan Guru SD untuk Pengembangan Profesional Berkelanjutan di Kabupaten Ende - Klemens Mere (Lembaga Riset dan Inovasi Almatani, 2026)
Continuous Professional Development (CPD) is a systematic process that enables teachers to continuously enhance their pedagogical, professional, social, and personal competencies throughout their careers. This study aims to analyze the role of school principals in empowering elementary school teachers for continuous professional development in Ende Regency. The study employs a qualitative approach using a library research method. Library research is a research method intended to collect, review, and analyze various written sources relevant to the research focus in order to obtain a comprehensive conceptual and theoretical understanding. The findings indicate that school principals’ leadership plays a highly strategic role in empowering elementary school teachers to support continuous professional development, particularly in the context of basic education in regional areas such as Ende Regency. Principals who are able to perform their roles as instructional leaders and transformational leaders are proven to contribute significantly to the creation of a school climate that is conducive to teachers’ professional growth.